2022
DOI: 10.3390/jmse10040471
|View full text |Cite
|
Sign up to set email alerts
|

Constructal Design of an Overtopping Wave Energy Converter Incorporated in a Breakwater

Abstract: A numerical study was performed in the present work about an Overtopping Device Wave Energy Converter (OTD-WEC) with one and two ramps incorporated in a real breakwater. The Constructal Design method was applied to evaluate the effects on the average dimensionless overtopping flow of the degrees of freedom of the device with one and two ramps. In addition, a comparison was carried out among the different geometry configurations of the OTD-WEC to determine which one presents the best hydrodynamic performance. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Therefore, a twodimensional computational model was developed to simulate the operational principle of the device. It is worth mentioning that the 2-D numerical approach has been widely used for the investigation of WECs [18,21,22,38,43,44], including overtopping devices [6][7][8][9][10]13,15]. This simplification is reasonable especially for the overtopping WEC, since the physical phenomenon that occurred due to the incidence of waves can be adequately approximated as an in-plane problem.…”
Section: Problem Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a twodimensional computational model was developed to simulate the operational principle of the device. It is worth mentioning that the 2-D numerical approach has been widely used for the investigation of WECs [18,21,22,38,43,44], including overtopping devices [6][7][8][9][10]13,15]. This simplification is reasonable especially for the overtopping WEC, since the physical phenomenon that occurred due to the incidence of waves can be adequately approximated as an in-plane problem.…”
Section: Problem Descriptionmentioning
confidence: 99%
“…Additionally, Di Lauro et al [12] performed numerical simulations based on the VARANS equations, aiming to investigate the hydraulic performance and structural stability of the innovative OBREC-V, and concluded that the proposed non-conventional geometry can promote significant improvements in wave energy extraction, reduction of the wave reflection, and hydraulic stability when compared with the traditional OBREC design. More recently, Martins et al [13], also applying the JONSWAP spectrum, developed a numerical study on an overtopping device with one and two ramps incorporated into a real breakwater, performing a geometric evaluation through the Constructal Design method. It should be highlighted that one can find several other studies addressing the overtopping devices and OBRECs with different approaches and goals, such as the studies by Liu et al [14], Barbosa et al [15], Contestabile et al [16], and Mariani et al [17].…”
Section: Introductionmentioning
confidence: 99%
“…The volume of fluid (VOF) method [34] is used to solve multiphase flow systems considering immiscible fluids and its main contribution was the introduction of the volumetric fraction in momentum equations. Subsequently, the method was improved and has been adopted for numerous wave energy investigations, not only for overtopping devices, but also for other types such as oscillating water column (OWC) and submerged plate [11,17,20,26,27,35].…”
Section: Mathematical Modelmentioning
confidence: 99%
“…The solutions obtained in this study were considered converged when the residuals of continuity and momentum equations in the x and z directions were lower than 10 −3 . A verification of the numerical methods employed in this study was previously performed by Martins et al [27], who compared results with the solution of the empirical model proposed by EurOtop [41].…”
Section: Numerical Modelmentioning
confidence: 99%
See 1 more Smart Citation